Bali Process dalam Menangani Penyelundupan dan Perdagangan Manusia di Indonesia (2016-2018) - Ivan Asbri Aplugi; Christian Herman Johan de Fretes; Roberto Octavianus Cornelis Seba (Jurnal Social Science, 2023)
This study aims to analyze the Bali Process cooperation forum to address human trafficking and smuggling issues in Indonesia in 2016–2018. The research method used is qualitative. The neoliberal approach is assisted by the multi-track concept used to analyze cooperative relations among member countries of the Bali Process. The results of the study explain that the Bali process is quite effective in assisting the handling of people smuggling cases in Indonesia through information exchange and policy dialogue, as well as increasing regional awareness and cooperation. increasing capacity building for law enforcers in member countries so that they can make a real contribution to the prevention and control of transnational crime, namely human smuggling, and trafficking.